Effect of surgical trauma on serum magnesium levels in the early postoperative period - Kalita, Rajeeb; Pande, Pradeep Kumar; Agrawal, Harikishan; Ravikanth, M. (International Journal of Research in Medical Sciences, 2017)
Background: For proper functioning of energy system in the body, magnesium is essential. Deficiency of magnesium leads to hyperactivity of central nervous system and neuromuscular system. During surgery or before surgery or after surgery there can be alterations in the volume of fluid and composition of electrolytes. Objective was to study the effect of surgical trauma on serum magnesium levels in the early postoperative period. Methods: The present hospital based cross sectional study was carried out for a period of one year among 35 cases of surgical stress and 10 normal as control. Institutional ethics committee permission was taken prior to the start of the study. Individual informed consent was noted from each individual patient from both cases and controls. Data was recorded in the pre-designed pre-tested semi structured questionnaire for the present study. Serum magnesium level was assessed in both the groups and compared. Results: It was found that the preoperative magnesium levels were more as compared to postoperative levels among both the types of stress groups but the difference was not found to be statistically significant (p > 0.05). Among the mild to moderate stress groups, it was found that the preoperative magnesium levels were more as compared to postoperative levels among all the age groups but the difference was not found to be statistically significant (p > 0.05). Among the severe stress groups, it was found that the preoperative magnesium levels were more as compared to postoperative levels among all the age groups but the difference was not found to be statistically significant (p > 0.05). Conclusions: Occurrence of postoperative hypomagnesaemia plays a minor role in normal surgical convalescence.